Revealing the Effectiveness of Tourism Development on Health in Asian Economies - Song, Yun; Su, Zhi-Wei; Tao, Ran; Umut, Alican (Frontiers in Public Health, 2022)
Most Asian economies consist of tourism attraction destinations. The traditional literature explores the cultural, social, and economic effects of tourism; thus, there exists a vacuum related to the impacts of tourism development on the human health of local people. Hence, the current study examines the impact of tourism development on health outcomes of the tourism-based selected Asian economies. The panel autoregressive distributed lag (ARDL) methodology is used to deduce the short-run and long-run impacts of tourism development on health outcomes. The results disclose that tourism activities insignificantly influence health outcomes in the short run. However, tourism development brings improvement in health outcomes in the long run. This research offers a new approach highlighting the significance of tourism development for human health and emphasizes the importance of tourism development for destination management and marketing.